SELF-DEVELOPMENT FACTORS FOR CHEMISTRY TEACHERS (Scientific journal of the Fergana State University, 2024)
In the article, the new educational paradigm proceeds from the fact that the development of lifelong learning skills is a continuous process, the importance of self-development competence of a chemistry teacher, stages of self-development, factors, experience — An analysis of the results of a survey conducted during experimental work is provided.